Level of Satisfaction with the Application of the Collaborative Model of the Flipped Classroom in the Sport of Sailing - Israel Caraballo Vidal; Luka Pezelj; Juan José Ramos-Álvarez; Francisco David Guillen-Gamez (Education Sciences, 2024)
The aim of this study was to assess student satisfaction levels when implementing the collaborative flipped classroom learning model in sailing-sports-related content. The sample consisted of eighty second-year students (21.9 ± 4 years old) pursuing a degree in Physical Activity and Sports Sciences. To evaluate student satisfaction levels, a validated self-assessment questionnaire was administered following completion of the various workshops. The language used was formal, objective, and clear, without biased or ornamental language. The survey comprised six questions, three of which were in the Likert format and three in the dichotomous format. These questions explored students’ viewpoints on participation, usefulness, and satisfaction regarding the implementation of this pedagogical approach. The findings indicate a significant degree of satisfaction and usefulness associated with the employment of this model for teaching sailing sports content. Moreover, students demonstrated a strong sense of engagement with their peers. The implementation of the flipped classroom teaching model among higher education students enhances their satisfaction levels while acquiring knowledge on sailing sports content.